(untitled) (The Conference Hub, 2025)
Reliable financial statements are crucial in contemporary business environments, serving as the primary information source for investors, creditors, regulators, and other stakeholders. Inaccuracies or misrepresentation in financial reporting can significantly harm organizational credibility and decision-making processes. Therefore, the implementation of robust internal and external control mechanisms is vital for ensuring the reliability and transparency of financial statements (Graham, 2020).